Improving Outcomes from Breast Cancer in a Low-Income Country: Lessons from Bangladesh. (5th December 2011) - Story, H. L.; Love, R. R.; Salim, R.; Roberto, A. J.; Krieger, J. L.; Ginsburg, O. M.
Abstract : Women in low- and middle-income countries (LMICs) have yet to benefit from recent advances in breast cancer diagnosis and treatment now experienced in high-income countries. Their unique sociocultural and health system circumstances warrant a different approach to breast cancer management than that applied to women in high-income countries. Here, we present experience from the last five years working in rural Bangladesh. Case and consecutive series data, focus group and individual interviews, and clinical care experience provide the basis for this paper. These data illustrate a complex web of sociocultural, economic, and health system conditions which affect womens' choices to seek and accept care and successful treatment. We conclude that health system, human rights, and governance issues underlie high mortality from this relatively rare disease in Bangladesh.